Facet-dependent catalytic performance of Au nanocrystals for electrochemical nitrogen reduction - Zhang, Weiqing (2022)
Nanostructured metal catalysts have attracted great interest due to their extraordinary performance for electrocatalysis including electrochemical nitrogen reduction (ENRR). However, their working mechanisms for ENRR are still not fully understood. Herein, seven monofaceted polyhedral Au nanocrystals were synthesized and systemically compared to elucidate the relation between Au crystal facets and NRR performance. It is found that polyhedra with high-index facets catalytically outperform those with low-index facets. Specifically, Au nanostars enclosed with (321) facets show a high NH3 production rate of 2.6 μg h-1 cm-2 (20 μg h-1 mg-2) and faradaic efficiency of 10.2% at -0.2 V, which are 3.1- and 5.1-folds larger than those of nanocubes enclosed with (100) facets. As revealed by theoretical investigation, a larger energy barrier for reduction of H+ to H* (ΔGH*) hinders occurrence of HER on the Au(321) surface, thus ensuring better NRR selectivity. Meanwhile, a lower energy barrier for formation of N2H2* on the catalyst surface and a larger energy barrier for decomposing the formed N2H2* back into N2 and 2H* jointly favor a higher NH3 production rate. This study provides mechanistic insights into ENRR and rational design of metal nanocrystals for electrocatalysis.